Dampak Kolonisasi Terhadap Penduduk Asli Australia : Sejarah dan Implikasinya - Handika Anggit Pramudya; Eko Ribawati (Pusat Riset dan Inovasi Nasional, 2025)
This study has 2 (two) objectives. The first study aims to find out the history of the arrival of the British to Australia. The second study aims to find out the influence of British colonization on the Indigenous tribe. This will reveal what kind of colonization was carried out by the British so that the Indigenous tribe was marginalized from its original area of ​​population, even its existence was almost extinct. Since the arrival of Arthur Philip in the late 18th century was the beginning of British colonization in Australia. Where at that time the Australian region was only a wilderness that the British considered the right area to be used as a shelter for British defenders. Sending settlements and civil servants to Australia. Finally, a population area was formed like a structured country that can be seen from several policies implemented by the British at that time. However, long before the arrival of the British to the Australian region, Australia had formed an indigenous Australian tribe. The method used by the researcher is historical research which has four stages: heuristic, critical, interpretation and historiography. The author utilizes library sources by searching for journals, books and others for reference.